“Effectiveness Of Self-Instructional Pamphlet On Mental Health Literacy Among Women In Selected Rural Community.Chennai” - Rejili Grace Joy.M; Dr. Kavinmozhi James; VahithaMala.K; Nivetha.N; Minusri IV; Nivethitha M; Nadhiya.S (Revista Electronica de Veterinaria, 2024)
This study investigates the effectiveness of a self-instructional pamphlet in enhancing mental health literacy among rural women in Thodukadu Rural Village, Chennai. Employing a pre-experimental one-group pretest-posttest design, the research involved 100 women aged 21 to 45 years, selected through convenience sampling. A self-structured questionnaire was utilized to assess participants’ mental health literacy before and after their exposure to the self-instructional pamphlet. Initial findings revealed that 87% of participants had low mental health literacy, with no individuals classified as having high literacy. After the intervention, results indicated a significant improvement, with 95% of participants achieving high mental health literacy. This improvement was evidenced by a mean pre-test score of 34.71 (SD = 4.53) compared to a post-test score of 75.31 (SD = 2.98), resulting in a statistically significant mean difference of 40.6 (t = 74.40, p < 0.001). While demographic factors such as age, education, and marital status did not show significant associations with literacy levels, a notable relationship was observed with religious affiliation (p = 0.024). These findings highlight the effectiveness of self-instructional pamphlets in raising mental health awareness and emphasize the need for culturally sensitive approaches to effectively improve mental health literacy among rural populations.